Study of Correlation of Arsenic in Fish Flesh And Occurrence of Oral Carcinoma in Effected Areas Of West Bengal - Basak, Tanmoy; Pal, Pritha; Sarkar, Subhasis (Journal of Mines, Metals and Fuels, 2023)
Arsenic has been associated with the occurrence of various carcinoma like skin, lung, bladder, kidney, liver, oral cavity. Its toxicity is reported to have been contributed through the intake of drinking water from various contaminated sources. However, its possible relationship with the intake of the metal contaminated fish flesh with the occurrence of carcinoma has not yet been well established. 83 oral malignant and 80 control individuals were selected for the study and on their proper consent, the hair samples were processed for arsenic estimation by the method of flow injection hydride generation atomic absorption spectrometry. The data related to the determination of arsenic level in fish flesh obtained from the affected districts of West Bengal was collected from the literature. The statistical analysis of all the data was performed by using SPSS Version 10.1, which suggested a highly significant large positive correlation between the intake of arsenic contaminated fish and the occurrence of oral malignancy in the affected individuals (p value = 0.023). The study concludes that the intake of the metal contaminated fish can be a possible factor leading to the malignancy of the selected population.